MODAL SOSIAL KELOMPOK WANITA TANI (KWT) TERHADAP KESEJAHTERAAN KELUARGA DI DESA RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Yusra Fadilah Nur Siregar; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The research was entitled "Social Capital of Women Farmer Groups (KWT) For Family Welfare in Rimbo Panjang Village, Tambang District, Kampar Regency. This study takes the theme of discussion related to social capital and the welfare of farming families because the important role of social capital in a group is very large and its relation to the welfare of family members of farmers is also large. Analysis of the data used in the study used a descriptive quantitative method, which discussed the elements of social capital and welfare as well as welfare measurement tools, namely income, education and health services. The formulation of the problems discussed in this research are (1) How is social capital in farmer groups in Rimbo Panjang Village? (2) What is the level of family welfare of farmer members in Rimbo Panjang Village? Data collection techniques used are questionnaires, observation and documentation. The population found in the field was 60 farmer members, then using the saturated sampling method, the sample used was 60 people or all members of the group. The results of research from the field can be concluded that the social capital of group members is at a moderate level for that norms and values and beliefs must be further enhanced, and for networks the quality must be maintained. In addition, the level of family welfare of farmer members is at a moderate level and enters the stage III of the prosperous family stage by assessing and looking at the existing welfare indicators. Keywords: Social Capital, Social Welfare, Women Farmer Groups